CONTACT STRESS ANALYSIS AND OPTIMIZATION OF DOUBLE SHOCK SLEEVE MOVABLE TOOTH - SHEN HaiTao; AN ZiJun (Jixie qiangdu)
The movable tooth in the double shock sleeve movable tooth transmission structure is an indispensable part,which is easy to fail. The contact stress analysis of the movable tooth is of great significance to improve the bearing capacity and service life of the mechanism. The contact surface pressure and subsurface stress field distribution of movable teeth are solved by numerical method. The results show that the contact stress will appear singularity and stress concentration,which seriously affect the transmission performance of the transmission mechanism. In this paper,the logarithmic generatrix modification method and genetic optimization algorithm are used to optimize the structure of sleeve movable teeth. The results show that this method can effectively improve the contact stress singularity and stress concentration of movable teeth. The research results can provide theoretical guidance for the structural design and optimization of double shock sleeve movable tooth transmission and line contact parts.